Scientific predication of management of innovative systems of construction enterprises - Khomenko, N. (Ways to Improve Construction Efficiency, 2018)
The article deals with theoretical aspects of management of innovative systems of construction enterprises. At the same time, the choice of the method for assessing the effectiveness of innovations and the successful implementation of the innovative development of a construction enterprise are determined by the specific goals and objectives of innovation policy. The analysis of technological innovations, problems of their implementation on the levels of construction enterprises.